The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.funeco.2016.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Host specificity and diversity of Amylostereum associated with Japanese siricids

Abstract: The mutualism between siricid woodwasps and Amylostereum fungal symbionts has long been considered to be species-specific. Recent studies from North America have challenged this assumption, where native siricids and the introduced Sirex noctilio are clearly swapping symbionts. Whether this pattern is a consequence of invasion or an underappreciated property of siricid biology is unknown. Here we show that the native Japanese siricid, Sirex nitobei, carries both Amylostereum areolatum and Amylostereum chailleti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Here, we describe trends in genomic architecture and gene content in twenty representative species of Russulales. Our dataset contains fourteen previously unanalyzed genomes, including 11 species of ECM Russulaceae and their saprotrophic sister group ( Gloeopeniophorella convolvens ), and Amylostereum chailletii , a white-rot wood-decomposer that is associated with siricid woodwasps in a timber pathogenic symbiosis (Fitza et al 2016). Our analysis elucidates patterns of functional diversity that have evolved within the ECM symbiotrophs, including evolution of PCWDEs, retention of genes to scavenge nitrogen compounds in soil organic matter, secondary metabolism, and TE invasion favoring duplication of species-specific genes.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we describe trends in genomic architecture and gene content in twenty representative species of Russulales. Our dataset contains fourteen previously unanalyzed genomes, including 11 species of ECM Russulaceae and their saprotrophic sister group ( Gloeopeniophorella convolvens ), and Amylostereum chailletii , a white-rot wood-decomposer that is associated with siricid woodwasps in a timber pathogenic symbiosis (Fitza et al 2016). Our analysis elucidates patterns of functional diversity that have evolved within the ECM symbiotrophs, including evolution of PCWDEs, retention of genes to scavenge nitrogen compounds in soil organic matter, secondary metabolism, and TE invasion favoring duplication of species-specific genes.…”
Section: Introductionmentioning
confidence: 99%
“…Preference for this fungal strain by S. nigricornis in the present study is consistent with the fact that larvae of this native Sirex are known to develop in the same trees as S. noctilio (Long et al ., ; Ryan et al ., ; Hajek et al ., ) and horizontal transmission of Amylostereum between Sirex species appears to occur within trees (Hajek et al ., ; Wooding et al ., ). Sirex species were previously considered specific to single Amylostereum species (Talbot, ; Gilbertson, ), although studies of Sirex and Urocerus have demonstrated flexibility in the Amylostereum species being carried (Wooding et al ., ; Fitza et al ., ; Hajek et al ., ), in particular by two Sirex native to North America, including S. nigricornis (Hajek et al ., ; Olatinwo et al ., ). Although relatively little is understood about the biology and behaviour of S. nigricornis , flexibility in symbiont use could be advantageous now that the competitive S. noctilio is present.…”
Section: Discussionmentioning
confidence: 99%
“…The fungus vectored by S. nitobei is either Amylostereum areolatum (Chaillet ex Fries) Boidin (in most cases) or A. chailletii (Pers.) Boidin (Kobayashi et al., 1978 ; Fitza et al., 2016 ; Wang et al., 2021 ). There are no records of both fungi being found together in any individual wasp.…”
Section: Pest Categorisationmentioning
confidence: 99%
“…No intraspecific diversity is reported for S. nitobei . However, the symbiotic fungus species has been observed to vary between individuals, with associations with either Amylostereum areolatum or A. chailletii (Fitza et al., 2016 ). Intraspecific variation within A. areolatum has also been observed.…”
Section: Pest Categorisationmentioning
confidence: 99%